O custo de transação do despacho aduaneiro de importação na formação de preço das mercadorias - Lobo, Bruno Eduardo Budal (2024)
All goods crossing Brazilian borders must undergo customs inspection, which is essential to ensure regulatory compliance and the objectives of foreign trade policy. In Brazil, this control is constitutionally assigned to the Ministry of Finance, with the Federal Revenue Service overseeing clearance procedures. Historically, the extrafiscal function was prioritized, but revenue collection has become the primary focus in recent years. However, Brazilian customs legislation exhibits weaknesses, such as political sanctions, lack of clarity in obligations, and disregard for the importer’s good faith. The establishment of CEJUL, an administrative tribunal composed exclusively of Federal Revenue officials, has amplified criticism of the system, as it conducts virtual judgments without published justifications, violating constitutional principles and international agreements. This repressive stance increases transaction costs and the final price of goods, benefiting the State through higher tax revenue but perpetuating institutional behavior that diverges from regulatory objectives and international best practices.